2020
DOI: 10.1021/acs.inorgchem.0c01160
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Assisted Hierarchical Aggregation of Dawson-type Polyoxometalate in the Presence of {Re6Se8} Based Clusters

Abstract: The association of metallic clusters (CLUS) and polyoxometalates (POM) into hierarchical architectures is achieved using γ-cyclodextrin (γ-CD) as a supramolecular connector. The new self-assembled systems, so-called CLUSPOM, are formed from Dawson-type polyoxometalate [P2W18O62]6– and electron-rich rhenium clusters. It is worth noting that a cluster-based cation [{Re6Se8}­(H2O)6]2+ on one hand and a cluster-based anion on the other hand [{Re6Se8}­(CN)6]4– can be associated with the anionic POM. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Actually, this structure exhibits γ-CD-based rods in which two CDs encapsulate the {P2W18} unit forming a hybrid rod [{P2W18}@2(γ-CD)]n (see Figure 6A). In {P2W18}0.5{AlMo6}0.5(γ-CD), the primary face of γ-CDs interacts symmetrically with the two opposite caps of the {P2W18} anion as previously observed in the non-conventional host-guest assembly [{P2W18}@2(γ-CD)]@{Mo154} 15 or in the hierarchical three-component solid 53 built from {Re6Se8} cationic cluster, {P2W18} anion and γ-CD (see Figure S22 for detailed structural comparison). As anticipated, the insertion of the Dawson-type POM increases the space between γ-CDs, which manifests itself with the largest c parameter value.…”
Section: Toward Isoreticular Series Of Multi-component Cdbased Open F...mentioning
confidence: 58%
“…Actually, this structure exhibits γ-CD-based rods in which two CDs encapsulate the {P2W18} unit forming a hybrid rod [{P2W18}@2(γ-CD)]n (see Figure 6A). In {P2W18}0.5{AlMo6}0.5(γ-CD), the primary face of γ-CDs interacts symmetrically with the two opposite caps of the {P2W18} anion as previously observed in the non-conventional host-guest assembly [{P2W18}@2(γ-CD)]@{Mo154} 15 or in the hierarchical three-component solid 53 built from {Re6Se8} cationic cluster, {P2W18} anion and γ-CD (see Figure S22 for detailed structural comparison). As anticipated, the insertion of the Dawson-type POM increases the space between γ-CDs, which manifests itself with the largest c parameter value.…”
Section: Toward Isoreticular Series Of Multi-component Cdbased Open F...mentioning
confidence: 58%
“…In the supramolecular adduct {V 6 (NO 2 ) 2 }@2γ-CD, cyclodextrin host interacts with the POV unit through the primary faces as frequently reported for the inclusion complexes built from γ-CDs and Keggin and Dawson type polyoxometalates. [14,17,19,28] The inclusion complexes are stacked together along the a axis forming a bamboo-like arrangement (Figure 5B) within a network directed by hydrogen bonds (d O • • • O = 2.7À 3.1 Å) that interconnect secondary rims of neighbored 1 : 2 host-guest motifs. The space filling representation shows the full embedment of the POV into the cavity of the γ-CDs, while the organic tails point out the center of CDs cavity (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth to note that the chaotropic binding by CDs is not limited to POMs since this selfassembly process is also observed on other nanosized inorganic ions such as octahedral metal-atom clusters or dodecaborates. [21][22][23][24][25][26][27][28] Recent progresses in polyoxovanadates (POVs) chemistry demonstrate their potential interest for energy-related applications including small molecules activation, redox-flow or Liand Na-ion batteries. [29][30][31][32][33] Thank to their striking redox properties, POVs have been identified as appealing components for designing advanced materials such as resistive switching devices.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, a recent study on the influence of the cooperative phenomenon on volatile molecule sorption into giant POMs showed that they can be used as nanoscaled molecular-separating units. 16 In addition, the chaotropic effect-driven association of POMs with macrocyclic host molecules [17][18][19] makes them one of the key objects in modern supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%